2018
DOI: 10.2196/diabetes.9333
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a Digitally Delivered Low-Carbohydrate Type 2 Diabetes Self-Management Program: 1-Year Results of a Single-Arm Longitudinal Study

Abstract: BackgroundType 2 diabetes mellitus has serious health consequences, including blindness, amputation, stroke, and dementia, and its annual global costs are more than US $800 billion. Although typically considered a progressive, nonreversible disease, some researchers and clinicians now argue that type 2 diabetes may be effectively treated with a carbohydrate-reduced diet.ObjectiveOur objective was to evaluate the 1-year outcomes of the digitally delivered Low-Carb Program, a nutritionally focused, 10-session ed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
89
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(94 citation statements)
references
References 29 publications
3
89
0
2
Order By: Relevance
“…Of these, 15/29 used high‐frequency contact (defined as ≥2 sessions/month), 10/29 used moderate‐frequency contact (defined as ≥1 session/month), and 4/29 used low‐frequency contact (defined as <1 session/month). Five (5/40) studies reported the use of remote contact (eg, email, phone, web‐based application, online discussion boards) for the majority or all of the scheduled contact, or as a supplement to in‐person contact . One study offered participants a choice between remote and/or in‐person contact …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 15/29 used high‐frequency contact (defined as ≥2 sessions/month), 10/29 used moderate‐frequency contact (defined as ≥1 session/month), and 4/29 used low‐frequency contact (defined as <1 session/month). Five (5/40) studies reported the use of remote contact (eg, email, phone, web‐based application, online discussion boards) for the majority or all of the scheduled contact, or as a supplement to in‐person contact . One study offered participants a choice between remote and/or in‐person contact …”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies were randomized controlled trials, 17,21-37 three were non-randomized controlled clinical trials, 15,38,39 16 were single-arm intervention studies, 16,[18][19][20][40][41][42][43][44][45][46][47][48][49][50][51] two were retrospective case series analyses, 14,52 and two were case reports. 53,54 Thirty-four studies [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][32][33][34][36][37][38][43][44][45][46]…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 More recently, severe carbohydrate restriction has also gained attention due to the potential for T2D remission. 3,8,9 There has been much scientific interest in carbohydrate restricted diets to manage T2D, with at least 22 randomized control trials, 10 non-randomized control trials, and 10 systematic reviews (9 with meta-analyses) that have investigated the effects of carbohydrate restriction on glycemic control in patients with T2D. 10−13 While there is considerable heterogeneity in findings, this evidence generally shows that the lower carbohydrate dietary interventions are at least as effective as control diets for improving HbA1c, T2D medication requirements, body weight, and dyslipidemia.…”
mentioning
confidence: 99%
“…Studien zeigen, dass eine Beratung durch Ernährungsfachkräfte mit einer effektiveren Senkung des HbA1c assoziiert ist [3]. Digitale und qualitätsgesicherte Programmangebote haben ebenfalls das Potential bei einer Ernährungsumstellung zu unterstützen [10].…”
unclassified